2019
DOI: 10.3389/fmicb.2019.01384
|View full text |Cite
|
Sign up to set email alerts
|

A New Isolate of Pediococcus pentosaceus (SL001) With Antibacterial Activity Against Fish Pathogens and Potency in Facilitating the Immunity and Growth Performance of Grass Carps

Abstract: Probiotic-feeding continues to be a promising strategy to control the bacterial pathogens in aquaculture. A new Pediococcus pentosaceus strain (SL001) was isolated from 1000s of soil samples, which exhibited wide antimicrobial spectrum of against fish pathogens, involving Aeromonas hydrophila , Aeromonas veronii , Aeromonas sobria , Edwardsiella tarda , Lactococcus garvieae … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
35
0
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 52 publications
(39 citation statements)
references
References 64 publications
3
35
0
1
Order By: Relevance
“…P. pentosaceus SL001, isolated from many soil samples, not only greatly increased the expression of complement 3 and immunoglobin M but also ameliorated damage to the intestinal villi and goblet cells, indicating promotion of the immune system of grass carp. Its broad-spectrum antibacterial properties also provided an opportunity for probiotic use in freshwater fish [ 19 ]. P. pentosaceus was found to be beneficial to mud crabs because of its bacteriostatic, immune-enhancing and growth-promoting virtues [ 68 ].…”
Section: Evidence Of P Pentosaceus Use In Food Enmentioning
confidence: 99%
See 1 more Smart Citation
“…P. pentosaceus SL001, isolated from many soil samples, not only greatly increased the expression of complement 3 and immunoglobin M but also ameliorated damage to the intestinal villi and goblet cells, indicating promotion of the immune system of grass carp. Its broad-spectrum antibacterial properties also provided an opportunity for probiotic use in freshwater fish [ 19 ]. P. pentosaceus was found to be beneficial to mud crabs because of its bacteriostatic, immune-enhancing and growth-promoting virtues [ 68 ].…”
Section: Evidence Of P Pentosaceus Use In Food Enmentioning
confidence: 99%
“…Promoting biological growth and storage [16][17][18][19][20] Inhibit bacteria and fungi without bacteriocins or BLISs P. pentosaceus T1, P. pentosaceus Z13P, P. Surviving manmade vaginal gel and producing antibacterial bacteriocin [58,59] system of grass carp. Its broad-spectrum antibacterial properties also provided an opportunity for probiotic use in freshwater fish [19]. P. pentosaceus was found to be beneficial to mud crabs because of its bacteriostatic, immune-enhancing and growth-promoting virtues [68].…”
Section: Referencesmentioning
confidence: 99%
“…A supplemented diet with P. pentosaceus enhanced the immunity of grass carp, increasing IgM and C3 (complement 3), whereas IL-8 was downregulated. Moreover, P. pentosaceus contributed to the elimination of pathogens and promoted grass carp growth rate [ 160 ].…”
Section: Bacteriocins As Immunomodulatorsmentioning
confidence: 99%
“…The effect of Pediococcus pentosaceus strain (SL001) in growth-related and immune-related genes was evaluated in grass carps. Results showed that the strain was able to enhance immunity and promoter growth of grass carps ( Gong et al, 2019 ). A recent study evaluated the effect of probiotic Chromobacterium aquaticum on zebrafish model.…”
Section: In Vivo Assessment Of Bacteriocinsmentioning
confidence: 99%